Emotions of subject and object affect beauty differently for images and music - Bruns, Anna; Pombo, Maria; Ripollés, Pablo; Pelli, Denis G. (Journal of vision (Charlottesville, Va.), 2023)
What role do the emotions of subject and object play in judging the beauty of images and music? Eighty-one participants rated perceived beauty, liking, perceived happiness, and perceived sadness of 24 songs, 12 art images, and 12 nature photographs. Stimulus presentation was brief (2 seconds) or prolonged (20 seconds). The stimuli were presented in two blocks, and participants took the Positive and Negative Affect Score (PANAS) mood questionnaire before and after each block. They viewed a mood induction video between blocks either to increase their happiness or sadness or to maintain their mood. Using linear mixed-effects models, we found that perceived object happiness predicts an increase in image and song beauty regardless of duration. The effect of perceived object sadness on beauty, however, is stronger for songs than images and stronger for prolonged than brief durations. Subject emotion affects brief song beauty minimally and prolonged song beauty substantially. Whereas past studies of beauty and emotion emphasized sad music, here we analyze both happiness and sadness, both subject and object emotion, and both images and music. We conclude that the interactions between emotion and beauty are different for images and music and are strongly moderated by duration.